A manual for writers of research papers, theses and dissertations Chicago style for students and researchers - Turabian, Kate L. (Chicago guides to writing, editing and publishing, 2007)
The author's practical advice on the successful completion and submission of the student research paper is preserved in this updated new edition of the classic reference that embraces the new modes of research, writing, and source citation brought about by the Internet.